Epidemiological profile of patients visiting private family medicine clinic in Kathmandu, Nepal - Thapa, Ashish; Amatya, Anugya; Parajuli, Roshan (Journal of General Practice and Emergency Medicine of Nepal, 2023)
Introduction: There are a lot of evidences supporting the important role of Family Physician/General Practitioner in the prevention of illness and death. In Nepal, Family Physicians are mostly limited to the Emergency Departments in the urban settings. The concept of Family Physician led primary care in urban setting is not known to most of the patient population. This study was conducted to know about the epidemiological profile of those patients visiting a family medicine clinic.Method: An observational, cross-sectional, quantitative study was conducted in a Family Physician lead primary care clinic in urban Nepal. All the patients attending the clinic for consultation from July 2023 to October 2023 were included in the study. Semi-structured questionnaire was used for the data collection. Data was then entered in MS EXCEL and analysis was done using Statistical Packages for Social Sciences (SPSS) version 16.Result: Total of 195 patients attended the clinic. The mean age of the patients was 46.01 ± 15.285 years. 52% of them were males whereas 48% were females. 12 out of 195 came for medical certificate and 183 of them came for consultation. Diabetes mellitus, Hypothyroidism and general health checkup were the top three reasons for consultation. Only six patients were from outside Kathmandu Valley. Majority of the patient population were from 31 – 40 age group.Conclusion: Average of two to three patients attended the clinic per day. There was equal male female distribution. Majority of the patients were from bread earners age group. Family physicians can have significant effect on the preventive and promotive aspect of health care and continued care for chronic diseases.